2021
DOI: 10.3889/oamjms.2021.6635
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, Risk Perception and Public Acceptance against Coronavirus Disease 2019 Vaccination in Indonesia

Abstract: BACKGROUND: The presence of a coronavirus disease 2019 (COVID-19) vaccine is very important to produce an immune response that slows down the pandemic. AIM: This study aims to find out more about the perspective of the Indonesian people which is predicted to affect vaccine acceptance by the public. METHODS: Quantitative research was conducted using an online survey via a Google form. The survey was conducted from January to February 2021. RESULTS: There were 225 respondents. The attitude of the community towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…In Indonesia, the first case of COVID-19 was on March 2, 2020; and in the city of Semarang, the first case was reported on March 17, 2020 [3] Moreover, various ways are done to reduce the transmission of the virus, among others, using standard face masks, maintaining physical distance, maintaining social distance, and finally vaccination against COVID-19 so that herd immunity can occur [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the first case of COVID-19 was on March 2, 2020; and in the city of Semarang, the first case was reported on March 17, 2020 [3] Moreover, various ways are done to reduce the transmission of the virus, among others, using standard face masks, maintaining physical distance, maintaining social distance, and finally vaccination against COVID-19 so that herd immunity can occur [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Semua produk Perusahaan di bidang Manufaktur Transportasi tersebut memiliki tingkat permintaan yang tinggi karena produk yang dihasilkan dipercaya Ini memiliki kualitas yang sangat baik, sehingga dipercaya oleh konsumen dalam dan luar negeri. Kondisi pandemi Covid-19 tidak mempengaruhi kepercayaan konsumen, sehingga proses produksi tidak terpengaruh akan kondisi yang ada, tidak terpengaruhnya kondisi dalam proses produk karena sudah sadarnya masyarakat akan pentingnya pengetahuan, perilaku serta praktik yang baik pada masyarakat (Pramana et al, 2020;Susilawaty et al, 2021) Meningkatnya permintaan konsumen terhazadap suatu barang menjadi latar belakang kebutuhan percepatan suatu proses produksi. Dalam menghasilkan produk tersebut, perusahaan membagi tiap tahapan produksi menjadi beberapa bagian yaitu Pengerjaan plat, Produksi, Pengecatan, Pemasangan komponen, Permesinan, Interior, Quality Control, Perencanaan dan Pengendalian produksi dimana sebagian besar proses pekerjaannya adalah penyambungan beberapa material plat, besi dan baja yang dilakukan dengan metode pengelasan.…”
Section: Pendahuluanunclassified
“…New hope for Indonesian citizens in 2021 due to the start of the vaccine program in Indonesia [8]. Total target of vaccination in Indonesia is 181,554,468 people [9]. Until September 2021, more than 18% population in Indonesia has been fully vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…Public perception of health and disease prevention is an important factor in the success of the Covid-19 vaccination program [9]. Initial survey on preparations for Covid-19 vaccination in Indonesia showed that 74% of respondents agree to receive Covid-19 vaccination [11].…”
Section: Introductionmentioning
confidence: 99%